Kufa and Kells: the illuminated word as sign and presence in the seventh-ninth centuries - Bongianino, U; Tilghman, BC (British Museum Press, 2021)
A volume exploring the ramifications of placing objects first and foremost in the comparative study of religions in late antiquity.